PENINGKATAN MINAT BELI KONSUMEN MELALUI DAYA TARIK IKLAN DAN LABEL HALAL PRODUK LIPCREAM EMINA PADA UNIVERSITAS MUHAMMADIYAH TANGERANG - Yuliyzar, Ismayudin; Enjelita, Shely Devi (Universitas Muhammadiyah Tangerang, 2020)
Women certainly want to always look beautiful wherever and whenever. A lot is being done to get the look you want to look good. The most common thing done for women is to use cosmetic products. Not too many people are still not paying attention to the safety and halalness of a product. This study aims to analyze the influence of the Attractiveness of Advertising and Halal Labels on Consumer Purchase Interest at the University of Muhammadiyah Tangerang. The sample of this study was 80 customer respondents at the University of Muhammadiyah Tangerang from a population of 425 customers. The method used is a quantitative method. Primary data collection was obtained from distributing questionnaires. The results showed that partially the Attractiveness of Advertising variable (X1) had a positive effect on Consumer Purchase Interest (Y) and the Halal Label (X2) has a positive effect on Consumer Purchase Interest (Y). And simultaneously the Attractiveness of Advertising variable (X1) and Halal Label (X2) has a positive effect on Consumer Purchase Interest (Y).